Pengaruh Kompetensi Sosial dan Kemampuan Menyusun Perangkat Pembelajaran terhadap Kompetensi Pedagogik dan Profesional - Yulia Aulia Rahmah; Budiyono Budiyono; Teguh Wibowo (Universitas Muria Kudus, 2020)
This study was used to determine the effect of social competence and the ability to compile learning devices on pedagogical and professional competencies of students in the Mathematics Education Study Program. This research leads to the problem of social competence towards pedagogic and professional competence, the ability to develop learning tools towards pedagogic and professional competence. This type of research is associative quantitative. The research was carried out in high school / vocational high school as a place for students of Mathematics Education Study Program FKIP Muhammadiyah University Purworejo 2019/2020. The sample used in this study was 32 students. The method of data collection uses documentation of the value of apprenticeship 1, 2 and 3. Data processing techniques use product moment correlation test and simple regression analysis. As a prerequisite test, normality and homogeneity tests were performed. For the requirements analysis, a significance test and linearity test were performed. The results of this study are (1) there is a positive and significant influence between social competencies on pedagogical and professional competencies; (2) there is a positive and significant influence between the ability to compile learning devices on pedagogical and professional competence